Multidisciplinary Approaches to Language Production - Habel, Christopher; Pechmann, Thomas; Habel, Christopher (Mouton de Gruyter, 2011)
Biographical note: Thomas Pechmann is Professor at the University of Leipzig, Germany. Christopher Habel is Professor at the University of Hamburg, Germany.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Sprachproduktion